Effects of Allicin on Late Sodium Current Caused by ΔKPQ-SCN5A Mutation in HEK293 Cells - Chen, Yating; Huang, Yun; Bai, Jing; Liu, Chuanbin; Ma, Shanshan; Li, Jiaxin; Lu, Xu; Fu, Zihao; Fang, Lihua; Li, Yang; Zhang, Jiancheng (Frontiers in Physiology, 2021)
Aim: The aim was to study the effect of allitridum (All) on the heterologous expression of late sodium current on ΔKPQ-SCN5A mutation in HEK293 cells, with a view to screening new drugs for the treatment of LQT3 syndrome. Methods and Results: The ΔKPQ-SCN5A plasmid was transiently transferred into HEK293 cells by liposome technology, administered by extracellular perfusion, and the sodium current was recorded by whole-cell patch-clamp technology. Application of All 30μM reduced the late sodium current (INa, L) of the Nav1.5 channel current encoded by ΔKPQ-SCN5A from 1.92±0.12 pA/pF to 0.65±0.03 pA/pF (P<0.01, n=15), which resulted in INa,L/INa,P decreased from 0.94%±0.04% to 0.32%±0.02%. Furthermore, treatment with All could move the steady-state deactivation of the channel to a more negative direction, resulting in an increase in channel deactivation at the same voltage, which reduced the increase in window current and further increases the deactivation of the channel intermediate state. However, it had no effect on channel steady-state activation, deactivation mechanics and recovery dynamics after deactivation. Conclusion: All reduced the late sodium current of ΔKPQ-SCN5A, which mechanism may be related to the increase of channel steady-state inactivation and intermediate state inactivation by the drug, thus reducing the window current.